Xylitol Obtained by Fermentation of Hydrolysate from Steam Explosion of Vetiveria zizanioides Nash - Chuntranuluck, Sawitri; Vaithanomsat, Pilanee; Rodkamnerd, Suwichaya (Agriculture and Natural Resources, 2013)
Xylitol is one of the most expensive polyol sweeteners with speciﬁ c health claims. Xylitol can be obtained from the hemicelullosic fraction of lignocellulosic materials containing xylose, such as vetiver grass (Vetiveria zizanioides Nash). Steam explosion is an efﬁ cient process for the fractionation of the main components of lignocellulosic residues. Vetiver grass was steam exploded at 17 kg.cm-2 (208 °C) for 5 min and hydrolyzed with 1% weight per volume (w/v) sulfuric acid at 120 °C for 45 min. Hydrolysate with 6.528 g.L-1 xylose was obtained. The inhibitory by-products in the hydrolysates affecting the bioconversion of the xylose into xylitol were acetic acid, 5-hydroxymethylfurfural, furfural and phenolic compounds. These inhibitory by-products were reduced by the addition of 10% (w/v) activated carbon under agitation (250 rpm) for 4 hr. After the detoxiﬁ cation treatment, acetic acid, 5-hydroxymethylfurfural, furfural and phenolic compounds were reduced by 47.5, 92.5, 98.7 and 14.3%, respectively. Then, the detoxiﬁ ed hydrolysate was used as the fermentation medium for xylitol production by C. guilliermondii FTI 20037; the xylitol yield per amount of xylose and productivity was 0.359 g.g-1 and 0.110 g.L-1.hr-1, respectively. When comparisons were made with pure xylose as a substrate, the xylitol yield and productivity was 0.662 g.g-1 and 0.379 g.L-1.hr-1, respectively.